FRMPD4 mutations cause X-linked intellectual disability and disrupt dendritic spine morphogenesis. (18th December 2017) - Piard, Juliette; Hu, Jia-Hua; Campeau, Philippe M; Rzońca, Sylwia; Van Esch, Hilde; Vincent, Elizabeth; Han, Mei; Rossignol, Elsa; Castaneda, Jennifer; Chelly, Jamel; Skinner, Cindy; Kalscheuer, Vera M; et al.
Abstract: FRMPD4 (FERM and PDZ Domain Containing 4) is a neural scaffolding protein that interacts with PSD-95 to positively regulate dendritic spine morphogenesis, and with mGluR1/5 and Homer to regulate mGluR1/5 signaling. We report the genetic and functional characterization of 4 FRMPD4 deleterious mutations that cause a new X-linked intellectual disability (ID) syndrome. These mutations were found to be associated with ID in ten affected male patients from four unrelated families, following an apparent X-linked mode of inheritance. Mutations include deletion of an entire coding exon, a nonsense mutation, a frame-shift mutation resulting in premature termination of translation, and a missense mutation involving a highly conserved amino acid residue neighboring FRMPD4-FERM domain. Clinical features of these patients consisted of moderate to severe ID, language delay and seizures alongside with behavioral and/or psychiatric disturbances. In-depth functional studies showed that a frame-shift mutation, FRMPD4 p.Cys618ValfsX8, results in a disruption of FRMPD4 binding with PSD-95 and HOMER1, and a failure to increase spine density in transfected hippocampal neurons. Behavioral studies of frmpd4-KO mice identified hippocampus-dependent spatial learning and memory deficits in Morris Water Maze test. These findings point to an important role of FRMPD4 in normal cognitive development and function in humans and mice, and support the hypothesis that FRMPD4 mutations cause ID by disrupting dendritic spine morphogenesis in glutamatergic neurons.